Situation Report: Romania, 29 July 1976 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. CC Delegation on dealing with Citizens' Petitions and Suggestions 1971-1980 Electrical Energy Plan Targets Revised Downward Ceausescu-Zhivkov Meeting Climaxes Series of Romanian-Bulgarian Contacts Meeting of Romanian-Mexican Commission on Economic Cooperation